What to do when nurses hurt nurses : understanding and resolving relational aggression and bullying in nursing - Dellasega, Cheryl (Sigma Theta Tau International, 2019)
"Outside of nursing, most people believe bullies are native only to playgrounds and high school locker rooms. Unfortunately, bullies also frequent hospital units, ambulatory care centers, clinics, and even emergency departments. Their targets? Their own colleagues and peers. Most practitioners know that the old adage #x93;nurses eat their young#x94; is alive and well in the 21st century. This conflict saps energy, destroys teamwork, and hinders motivation. Worst of all, it can decrease the quality of patient care. This fully updated new edition, What to Do When Nurses Hurt Nurses, tackles topics ranging from social media and crucial communications to resiliency and stress management. It provides tools to help nurses create safer, more respectful workplaces and combat the ongoing cycle of bullying. Cheryl Dellasega, author of the groundbreaking Surviving Ophelia, explores relational aggression and the nature of nurse-on-nurse violence while establishing an action plan for the future." -- provided by publisher.